Comparative Evaluation of Skeletal, Dental, Soft Tissue and Glenoid fossa Changes Induced by Fixed Functional (Rigid & Hybrid) and Myofunctional Appliances in Skeletal Class II patients - Paul, Rahul; Yadav, Deepti; Gulia, Vandana; Sharma, Ish Kumar; Gupta, Uchit; Saini, Prakher; Sawhney, Ratika (Journal of Neonatal Surgery, 2025)
Functional appliances have been used for over a century to correct Class II malocclusion, producing both dental and skeletal effects to reduce overjet in growing patients. This study aimed to evaluate and compare skeletal, dental, soft tissue, and glenoid fossa changes induced by fixed functional (Powerscope and Forsus Fatigue Resistant) and myofunctional appliances in 60 subjects divided into three groups. Pre-treatment (T0) and 6-month post-treatment (T1) lateral cephalograms were manually traced and analyzed. Results indicated statistically significant improvements with all appliances, with Powerscope showing prominent dentoalveolar changes (e.g., incisal inclination, U6-PP), myofunctional appliances demonstrating superior skeletal effects (e.g., Ar-Go-Me angle), and Forsus Fatigue Resistant contributing most to condylar remodeling (AE-SN and AE-CP angles). The study concludes that while all three appliances effectively correct Class II malocclusion, their efficacy varies: As for dentoalveolar correction, Powerscope appliance shows the maximum results, myofunctional appliances works best for skeletal correction, and Forsus for condylar remodelling along with skeletal correction, suggesting appliance selection should align with specific treatment objectives.